Why Rural Rich Remain Energy Poor - Mirza, Bilal; Kemp, Rene (Consilience, 2011)
The paper explores the rationale behind the complexities of energy poverty among different income groups in rural communities. We attempted to explain why rural rich, despite their relatively high purchasing power use energy sources which tend to categorize them as energy poor. Using the Energy Poverty Survey (EPS) – a dataset of more than 600 rural households from 27 different rural communities of Punjab, Pakistan, we presented the energy access situation in rural households among different income groups. Subsequently, we used binary logit regressions to assess the influence of access factors on energy source choices among different income groups. The influence of occupation and household income, membership and size is also assessed. The limited significance of household income for traditional biomass use and high significance of community remoteness indicators imply that households give high importance on the proximity of energy sources available to them and, in many cases, will prefer to be in the state of energy poverty, than to use a modern energy source like liquefied petroleum gas (LPG).